Desarrollo de una herramienta informática para la generación de un cuadro de mando integral en la gerencia de proyectos civiles (2016)
The research of the degree project has as general objective develop a computer tool that systematizes and optimizes the Generation of a balanced scorecard under the methodology of the Balanced Scorecard, as a central element of the Project management and performance measurement in a management Civil projects. The Integral Scoreboard is presented as a tool for Facilitate decision-making and continuous improvement by communicating Expedited form, the situation of the management of the most critical processes of a Portfolio of projects, generated for the purpose of achieving the objectives Established within the company's Strategic Plan.The research, framed under the methodological approach of research Applied in the feasible project modality, it is developed through the Implementation of the following specific objectives: A) Diagnose the current system of the company by analyzing the Information contained in the mission, vision, policies, values ??and objectives Strategic objectives and present the specific goals to which the portfolio Projects managed by the Project Management; B) Elaborate a matrix of characterization of the Project Management Civil society, in accordance with its objectives and functions, where its Processes, customers, suppliers and supplies, services and products Resulting, and identifying the key success factors and determining the strengths, Weaknesses, threats and opportunities of this management as a unit of Project management, based on your financial, human,Internal processes and relationships with internal and external lients; C) Develop a strategic map with its cause-effect relationships, a being Applied to the management of civil projects anaged by the Projects, which group strategies Definitions and proposals for the creation of Value, from the rspective:financial, customers, their processes Internal and innovation and learning; D) Financial and non-financial management indicators forms, to be located in Each of the four perspectives of the WCC, linked to the strategic map a being applied to the management of civil projects; E) To elaborate the structure of work decomposition (EDT) of the project; F) Develop the communication plan of the project; G) To elaborate a scientific project based on the present project for a Indexed journal;G) Establish a computer tool for an efficient Handling of the Balanced Scorecard.